2016
DOI: 10.1037/a0040100
|View full text |Cite
|
Sign up to set email alerts
|

Social (dis)order and psychosocial trauma: Look earlier, look outside, and look beyond the persons.

Abstract: The most common and extreme suffering humankind has ever experienced comes from interpersonal and collective intentional violence. In dealing with traumatic outcomes psychology must overcome the mutually constitutive interaction between the (dis)order of a given macro or microsocial context and the mental health of the persons living in it. Social psychologist Ignacio Martín-Baró addressed in a preferential way the study of civil war in El Salvador in terms of intergroup hostility and polarization. He also app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 46 publications
1
40
0
14
Order By: Relevance
“…Finally, as expected, victims exposed directly (vs. indirectly) reported less PWB and SoWB. These results are in line with the Psycho-Social Model of Trauma [ 17 , 46 ], which postulates that traumas caused by intentional violence have accumulating and enduring emotional, social, and political consequences. Therefore, the impact of direct (vs. indirect) traumas on victims’ health was greater, both from a psychopathological and positive function perspective.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Finally, as expected, victims exposed directly (vs. indirectly) reported less PWB and SoWB. These results are in line with the Psycho-Social Model of Trauma [ 17 , 46 ], which postulates that traumas caused by intentional violence have accumulating and enduring emotional, social, and political consequences. Therefore, the impact of direct (vs. indirect) traumas on victims’ health was greater, both from a psychopathological and positive function perspective.…”
Section: Discussionsupporting
confidence: 88%
“…However, only a few trauma victims develop psychopathology (e.g. PTSD; [ 17 , 18 ]) and many who initially develop PTSD recover over time without clinical treatment [ 19 ]. To explain these results, Foa and her colleagues suggested that PTSD is a consequence of disruptions in the normal processes of recovery related to dysfunctional cognitions (Emotional Processing Theory, EPT [ 12 , 20 ]).…”
Section: Introductionmentioning
confidence: 99%
“…As we have already noted, violence against nurses should be understood as a way of collective violence (WHO, 2002, p. 215). In this case the emotional impact should be defined as psychosocial trauma (Blanco et al, 2016) rather than a strictly psychic trauma, as it is presently construed.Even though the hurt and emotional impact of violence on health workers has not commanded the attention of many researchers (e.g., Hills and Joyce, 2013), in the future this should be a central research topic.It should be put in place institutional policies of assistance and support against violence and, above all, to endow them with real effectiveness. In other words, it is of utmost importance to recover the trust of nurses in health institutions and organizations they belong or where they work, something that the present research has found wanting in most countries.Following the European Foundation for the Improvement of Living and Working Conditions (Eurofound, 2016) is highly desirable to take organizational climate as a framework to explore original forms of intervention.…”
Section: Main Textmentioning
confidence: 99%
“…As we have already noted, violence against nurses should be understood as a way of collective violence (WHO, 2002, p. 215). In this case the emotional impact should be defined as psychosocial trauma (Blanco et al, 2016) rather than a strictly psychic trauma, as it is presently construed.…”
Section: Main Textmentioning
confidence: 99%
“…History marks them: the more than 60 years of violence caused by a sociopolitical conflict that has not ceased. Collective violence is a phenomenon of great instrumental and emotional impact (Arendt, 2005;Blanco et al, 2016). The depth of the sequelae generated by this phenomenon has strong repercussions at an individual level, in terms of the destruction of a life project, and at a collective level, in the destruction or reformulation of social and support networks (Thompson and Walsh, 2010).…”
Section: Introductionmentioning
confidence: 99%